Analyze Performance of Double Acting Tanker While Running Astern in Ice Condition - Afrizal, Efi; Koto, Jaswar (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2017)
The increasing of shipping activities through the Northern Sea Route (NSR) and growth of oil and gas activities in Arctic and Sub-Artic regions require suitable design of ice-going ships and planning operations in ice. In 2002, Sumitomo Heavy Industries has built advanced ice-ship called "Double Acting Tanker". This paper discussed application of new method to determine ice resistance of Double Acting Tanker running ahead in ice condition. The simulation was carried out at 1 m ice thickness in unfrozen and frozen channels and 0.5 m ice thickness in level ice condition. The simulation results were compared with experimental results.